TRANSITIONAL JUSTICE, RIGHT TO THE TRUTH AND HUMAN RIGHTS: case Gomes Lund and others (Araguaia Guerrilha) x Brasil - Tramontina, Robison (Unoesc International Legal Seminar, 2017)
On December 14, 2010, the Inter-American Court of Human Rights had announced the sentence Case "Araguaia Guerrilla" x Brazil, which considered null the interpretation given by the Supreme Court to the Amnesty Law. The Inter-American Court of human rights decision has generated controversy in the political and legal ambit. The main point of contention lies in the question of criminal prosecution. With the decision of the Inter-American Court Brazilian state should encourage and promote the accountability of state agents who have committed serious crimes during the military government (1964-1985). But such a procedure is not possible according to the decision of the Brazilian Supreme Court. This article is to analyze the arguments used by the Ministers of the Brazilian Supreme Court in ADPF 153 (Ação por Descumprimento de Preceito Fundamental) informed by literature and judicial decision on transitional justice and the right to the truth.